Cell Delivery: Routing Nanomolar Protein Cargoes to Lipid Raft‐Mediated/Caveolar Endocytosis through a Ganglioside GM1‐Specific Recognition Tag (Adv. Sci. 4/2020). Issue 4 (19th February 2020) - Imre, Norbert; Hetényi, Anasztázia; Szabó, Enikő; Bodnár, Brigitta; Szkalisity, Abel; Gróf, Ilona; Bocsik, Alexandra; Deli, Mária A.; Horvath, Peter; Czibula, Ágnes; Monostori, Éva; Martinek, Tamás A.
Abstract : In article number 1902621, Tamás A. Martinek and co‐workers develop a pentapeptidic tag, which reads the glycan code of ganglioside GM1 and triggers lipid raft‐mediated endocytosis, avoiding lysosomal entrapment. This carrier molecule can deliver macromolecular cargoes (e.g., IgG complexes) into live cells with the possibility to escape to the cytosol.